Tricyclic Antidepressants as Prophylactic Treatment for Tension-Type Headache - Martins, Lorena do Carmo de Souza; Almeida, Rodrigo Franklin Pinheiro; Menezes, Letícia Soares Teles de; Carvalho, Fabiane Caxias de Paula; Santos, Ana Flávia Resende; Tomaz, Sara Brenda de Souza (Headache Medicine, 2023)
Full abstract in PDF.